THE EFFECT OF EMOTIONAL INTELLIGENCE AND COMMITMENT ON PERFORMANCE THROUGH JOB SATISFACTION - Ardiani, Gusti Tia (Jurnal Ekonomi Manajemen, 2023)
The purpose of the research that has been carried out is to determine and analyze the effect of emotional intelligence and commitment on performance through job satisfaction of non-manager employees of PT. Sinar Sosro Tasikmalaya Branch Office. The research method used is a survey method, the data obtained directly through the distribution of questionnaires to 30 non-PT employees. Sinar Sosro Tasikmalaya Branch Office. Sampling using the census and the analytical method used in this study is path analysis to determine the direct and indirect effects of emotional intelligence, commitment, satisfaction and performance. Based on the research results, it is known that emotional intelligence and commitment have a significant effect on job satisfaction; emotional intelligence, commitment and job satisfaction have a significant effect on employee performance; and emotional intelligence, commitment has a significant effect on employee performance through job satisfaction of non-managers at PT Sinar Sostro Tasikmalaya Branch.